Tracheoesophageal Fistula in a COVID-19 Ventilated Patient: A Challenging Therapeutic Decision - Riccardo Rosati; Paola De Nardi; Antonio Dell’Acqua; Maria Rosa Calvi; Ugo Elmore; Elena Scarparo; Luigi Beretta (Case Reports in Surgery)
COVID-19 associated severe respiratory failure frequently requires admission to an intensive care unit, tracheal intubation, and mechanical ventilation. Among the risks of prolonged mechanical ventilation under these conditions, there is the development of tracheoesophageal fistula. We describe a case of a severe COVID-19 associated respiratory failure, who developed a tracheoesophageal fistula. We hypothesized that one of the mechanisms for tracheoesophageal fistula, along with other local and general risk factors, is the local infection due to the location of the virus itself in the tracheobronchial tree. The patient was managed successfully with surgical intervention. This case highlights the increased risk of this potentially life-threatening complication among the COVID-19 patient cohort and suggests a management strategy.